Endoscopic approach for a delayed post-traumatic ethmoidal mucocele: a technical note. (2nd January 2019) - Messerer, Mahmoud; Cossu, Giulia; Daniel, Roy Thomas
Abstract: Objective: Delayed post-traumatic mucoceles are rare. We describe the surgical treatment of a post-traumatic ethmoidal mucocele with intra-orbital extension. Method: A uninostril endoscopic endonasal approach (EEA) was performed. The access was contralateral to the lesion to provide a wider lateral view. After a large sphenoid and ethmoid sinuses opening, the collection was drained and the optic nerve precociously identified. The orbital roof was eroded and the frontal dura mater directly visible. Conclusion: The uninostril contralateral approach allows a good exposure of the lateral fields and is conservative towards the nasal mucosa. A favorable skull base anatomy is the prerequisite for its efficacy.